Investigating the Impact of Career Development, Organizational Commitment, and Organizational Support on Employee Retention - Shinta Ferdiana; Zafar Khan; Samrat Ray (Journal of Management Studies and Development, 2023)
This research examines the effect of career development, organizational commitment, and organizational support on employee retention among employees. The sample of 70 employees was selected from a population of 391 employees of a particular university using purposive sampling. A questionnaire was used to collect data on the four variables, which were analyzed using statistical techniques such as validity and reliability testing, multiple regression analysis, hypothesis testing, and coefficient of determination. The results indicate a significant simultaneous effect of career development, organizational commitment, and organizational support on employee retention. These findings support the expectancy theory and the social exchange theory, suggesting that organizations can improve employee retention by providing opportunities for career development, promoting organizational commitment, and providing support to their employees. The study highlights the importance of creating a positive work environment and fostering employee satisfaction for higher levels of employee retention.